(untitled) (Editora Impacto Científico, 2025)
This review article explores the application of CRISPR-Cas gene editing technology as a potential curative therapy for HIV infection. The introduction establishes the central problem: antiretroviral therapy (cART) suppresses HIV replication but does not eliminate the virus, which persists in a latent reservoir integrated into the genome of host cells. Eradication of this reservoir is the essential step toward a cure. In this context, the CRISPR-Cas system emerges as a promising tool, functioning as "molecular scissors" capable of removing or inactivating proviral DNA. The objective of the study is, therefore, to compile and analyze the current advances and challenges of this therapeutic approach. The methodology used was a narrative review of the literature, based on a search of the PubMed database for scientific articles published in the last five years, using the descriptors ’CRISPR-Cas’, ’HIV’, and ’Treatment’. The results and discussion are divided into two main strategies. The first is the direct attack on the viral genome, where CRISPR-Cas is used to excise or inactivate conserved sequences of HIV DNA, with the multiplex approach (use of multiple RNA guides) proving to be more effective. The second strategy focuses on modifying the host genome to create resistance to infection, with the main target being the knockout of the CCR5 co-receptor gene, inspired by cases of cure in patients who received bone marrow transplants from donors with a natural mutation in this gene. Despite success in cell and animal models, the review highlights significant challenges: the risk of viral escape through mutation, dangerous off-target effects (unwanted cuts in the human genome), the complex logistics of delivering the CRISPR system to all cells in the reservoir, and the possibility of an immune response against the Cas protein.